Analisis Penggunaan Bahasa Madura Tingkat Tinggi (Engghi Bhunten) oleh Siswa kepada Guru di UPTD SDN Pejagan 9 Bangkalan pada Lingkup Sekolah - Nor Arefa Suro; Noor Lailin Nisfah; Sulton Akbar; Muhammad Haykhal Priambudhi; Meilina Nuril Maulida; Selvia Dwiyanti; Ahmad Sudi Pratikno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The high-level Madurese language (engghi bhunten) is a form of linguistic politeness that reflects the values of respect and culture of the Madurese people. The use of this language has an important role in shaping character, communication ethics, and preserving local culture in the school environment. However, the use of engghi bhunten among elementary school students began to face various challenges due to limited vocabulary mastery and the dominance of the use of Indonesian in daily communication. This study aims to analyze the use of high-level Madurese language (engghi bhunten) by students to teachers at Unit Regional Technical Implementer of State Elementary Schools Pejagan 9 Bangkalan within the scope of the school. The research uses a qualitative approach with a descriptive type of research. Data was collected through observation and structured interviews with teachers and students of grade IV B. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study showed that students had used several engghi bhunten vocabulary when interacting with teachers, especially in learning Madurese language. However, its use has not been carried out consistently because students still experience difficulties in mastering vocabulary, pronunciation, and sentence composition. In addition, the use of the language is influenced by the family environment, peers, student background, and the habits of using the Indonesian language. Teachers play an important role in guiding and accustoming the use of polite language through example and direction during the learning process. Thus, the use of engghi bhunten not only serves as a communication tool, but also as a means of character formation and preservation of local culture in elementary school students.